Sympathectomy-induced blood pressure reduction in adult normotensive and hypertensive rats is counteracted by enhanced cardiovascular sensitivity to vasoconstrictors - Vavřínová, Anna; Behuliak, Michal; Bencze, Michal; Vodička, Martin; Ergang, Peter; Vaněčková, Ivana; Zicha, Josef (Hypertension research, 2019)
The effect of chemical sympathectomy on cardiovascular parameters and the compensatory role of adrenal hormones, the renin-angiotensin system, and cardiovascular sensitivity to vasoconstrictors were studied in spontaneously hypertensive rats (SHRs) and normotensive Wistar-Kyoto (WKY) rats. Sympathectomy was induced in 20-week-old rats by daily intraperitoneal guanethidine administration (30 mg/kg b.w.) for 2 weeks. Basal blood pressure (BP), heart rate (HR), and restraint stress-induced cardiovascular changes were measured by radiotelemetry. The BP response to catecholamines was determined in rats with implanted catheters. Sympathectomy decreased BP only transiently, and after 14-day guanethidine treatment, BP returned to basal values in both strains. Sympathectomy permanently lowered HR, improved baroreflex sensitivity, and decreased the low-frequency domain of systolic blood pressure variability (a marker of vascular sympathetic activity). Guanethidine also attenuated the BP and HR responses to restraint stress. On the other hand, the BP response to catecholamines was augmented in sympathectomized rats, and this was not due to the de novo synthesis of vascular adrenergic receptors. Sympathectomy caused adrenal enlargement, enhanced the expression of adrenal catecholamine biosynthetic enzymes, and elevated plasma adrenaline levels in both strains, especially in WKY rats. Guanethidine also increased the plasma levels of aldosterone and corticosterone in WKY rats only. In conclusion, sympathectomy produced a transient decrease in BP, a chronic decrease in HR and improvement in baroreflex sensitivity. The effect of sympathectomy on BP was counteracted by increased vascular sensitivity to catecholamines in WKY rats and SHRs and/or by the enhanced secretion of adrenal hormones, which was more pronounced in WKY rats.
Keywords: guanethidin; Cardiovascular Physiological Phenomena; nadledviny; Guanethidine; Restraint, Physical; zvířata; Heart Rate; Vasoconstrictor Agents; vazokonstriktory; baroreflex; Adrenal Glands; katecholaminy; Rats, Inbred SHR; Animals; Stress, Psychological; krysa rodu Rattus; Rats; Sympatholytics; potkani inbrední SHR; Blood Pressure; Catecholamines; Blood Vessels; krevní tlak; kardiovaskulární fyziologické jevy; sympatolytika; potkani inbrední WKY; srdeční frekvence; Baroreflex; psychický stres; Rats, Inbred WKY; fyzické omezení; Hypertension; hypertenze; cévy